Pengaruh Relaksasi Otot Progresif terhadap Penurunan Ansietas dan Peningkatan Kualitas Tidur Pasien Neurosa di Wilayah Kerja Puskesmas Kepanjen Kidul Kota Blitar - Nawang Wulandari; Titin Andri Wihastuti; Lilik Supriati (Journal of Ners and Midwifery, 2015)
Neurosa a psychic reaction with typical anxiety where clients are in fear that unconsciously displayed in various forms of behavior. Anxiety can leads physical imbalance such as increased blood pressure, insomnia, muscle tension and palpitations. Muscle tension and sleep difficulties are often experienced anxiety response. Some psychotherapy can be given to clients of anxiety one of which is progressive muscle relaxation therapy. The Â aims of this study was to determine the effect of progressive muscle relaxation therapy to decrease anxiety and improve the quality of sleep in patients neurosa in Health Center Area Kepanjen Kidul Blitar. Research design was quasy experimental Pre-Post Test With Control Group with purposive sampling. Number of samples 26 respondents were divided into control and treatment groups. Collecting data using questionnaires that have tested the validity and reliability. Results of analysis of anxiety and sleep quality was obtained p <0.05 in the treatment group and control before and after treatment, the difference in scores of anxiety and sleep quality of patients neurosa between the treatment group and the control group after a given intervention p <0.05. There is no correlation between the anxiety with the quality of sleep with p> 0.05. Therapy progressive muscle relaxation and deep breathing therapy can be used to reduce anxiety and improve sleep quality in patients neurosa.